2018
DOI: 10.1111/bcp.13524
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parallel regulatory–health technology assessment scientific advice on clinical development. Assessing the uptake of regulatory and health technology assessment recommendations

Abstract: One of the key findings of this analysis is that manufacturers tend to implement changes to the development programme based on both regulatory and HTA advice with regards to the choice of primary endpoint and comparator. It also confirms the challenging choice of the study comparator, for which manufacturers seem to be more inclined to satisfy the regulatory advice. Continuous research efforts in this area are of paramount importance from a public health perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 5 publications
0
38
0
Order By: Relevance
“…In 60% of cases, the comparators implemented would meet the needs of regulators and at least one HTA body involved in the advice and in 100% of cases for the primary endpoints. This supports the need to gather external input to support decision making for clinical trial design …”
Section: Parallel Advice Between European Regulators and European Htamentioning
confidence: 75%
“…In 60% of cases, the comparators implemented would meet the needs of regulators and at least one HTA body involved in the advice and in 100% of cases for the primary endpoints. This supports the need to gather external input to support decision making for clinical trial design …”
Section: Parallel Advice Between European Regulators and European Htamentioning
confidence: 75%
“…Similar initiatives to PRIME exist elsewhere, such as the breakthrough therapy designation program in the USA and the Sakigake Designation in Japan [33]. Increased early contacts and joint scientific advice with both regulators and HTA bodies should also be encouraged to identify the best comparator in clinical trials and facilitate the choice of primary end points that deliver added therapeutic value, which would ultimately accelerate access to new treatment options for cancer patients [34,35].…”
Section: • Improve Early Contacts Between Clinicians Regulators and Htamentioning
confidence: 96%
“…Following examination of comparator nonalignment, representative cases ( Table ) exemplifying impact of timely PSA on comparator divergence resolution have been highlighted by the EMA, whereby solutions obtained earlier in development yielded plans to satisfy the EMA and HTAB . A 2018 analysis revealed that the EMA and HTA collective comparator advice is implemented in only 60% of cases, with regulator advice being followed otherwise …”
Section: Ema‐htab Psa Pilot Case Studies and Program Development Impactmentioning
confidence: 99%
“…This begs for direct questions applicable and open to both the EMA and HTABs to discuss toward possible convergence and divergence clarification. Recent analyses on alignment of the EMA and HTAB feedback and degree of agreement by specific question domain (e.g., patient population and comparator) outline good examples to consider . The PC platform can then uncover views of each stakeholder on elements crucial to registration and market access and allow discussion on acceptable alternatives in cases of divergence.…”
Section: Ema‐htab Psa Pilot Case Studies and Program Development Impactmentioning
confidence: 99%